Anabolic-Androgenic Steroids - doi:10.5020/18061230.2007.p267 - Urival Magno Gomes Ferreira; Alan de Carvalho Dias Ferreira; Andréa Maria Pires Azevedo; Carlos Antonio Bruno da Silva (Universidade de Fortaleza, 2012)
There are evidences of the increase in the consumption of anabolic steroids and the damages to health caused by their indiscriminate use, mainly among children and youngsters. The anabolic-androgenic steroids (AAS) consist in testosterone and its derivatives. They are produced endogenously in the testicles and adrenal cortex and are responsible for the secondary sexual characteristics associated to masculinity. Although the results of the exogenous use of AAS are still controversial, they have been used for the increase of physical strength and muscle mass. These substances are directly related to different clinical conditions such as: bladder cancer, coronary disease, gynecomastia, hepatic disorders and cancer, and sterility. This study aimed at approaching relevant topics related to the drugs action mechanisms, ways of use and metabolism, and side effects, besides the importance of the prevention in the use of those drugs in most diverse age groups. The abusive use of anabolic-androgenic steroids consists in a problem that has gradually occurred, which has given rise to laws, rules and support groups turned to the prevention, education and restriction of their use.